Fabrication of Reinforcing Bars Made of Glass Fibers Reinforced with Polyester Polymer and Measurement of some of their Mechanical Properties - Aziz, Rodaina Miftah; Amjd Mussa, Al-Hames (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
This study investigates the tensile and bending resistance of reinforcing bars made from glass fibers with polyester resin as a binding material. The bars were fabricated using two methods: manual fiber winding after mixing with resin and manual casting in cardboard molds. Bars of lengths (50 cm) and diameters (8 mm, 10 mm, 12 mm) were produced. Testing revealed that manually wound samples with smaller diameters exhibit the highest tensile strength (400 MPa), with tensile strength values ranging from 30 to 40 kg/mm² depending on sample diameter. Bending resistance was found to be inversely proportional to radius. Tensile tests indicated that the samples belong to the category of semi-ductile materials. Additionally, tests showed that samples cast in cardboard molds failed due to non-uniform composition and the presence of air bubbles trapped inside the bars.